Faktor-faktor yang mempengaruhi minat mahasiswa akuntansi untuk mengikuti Pendidikan Profesi Akuntansi (PPAk) pada Perguruan Tinggi di Pekanbaru - Sri Susanti; Muhammad Rasuli; Al Azhar Lukman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine and explain the influence of career motivation, qualities motivation, economic motivation and social motivation on student interest in accounting to follow the accounting profession education. The population in this study is accounting students of Riau University, UIN SUSKA and Islamic Riau University, with a sample of 95 people from the economic faculty of the accounting students of Riau university, UIN SUSKA and Islamic Riau University forces in 2009 and 2010. Sampling was based on a purposive sampling method. The data of this study then processed using multiple regression method through the application of SPSS 20 statistical. The result of this study indicate that career motivation, qualities motivation and economic motivation significantly affect student interest in accounting for follow the accounting profession education. While social motivation does not affect the interest of accounting students to follow the accounting profession education. The determination of the coefficient (R square) in this study was 0,269. This figure shows that 26,9% student interest in accounting are influenced by career motivation, qualities motivation, economic motivation and social motivation. while the remaining 73.1 % explained by other variable.Keywords: career motivation, qualities motivation, economic motivation, social motivation,student interest in ccounting to follow the accounting profession education.